Criteria in Utilizing Engineered Wood in Residential Construction: A Community Preference Analysis - Eryonata Melino; Dewi Larasati; Hanson E Kusuma (DIMENSI (Journal of Architecture and Built Environment), 2025)
The phenomenon of global warming continues to intensify, with the construction sector emerging as a significant contributor due to its extensive use of non-biomass materials, which are major sources of carbon emissions. In response, engineered wood has gained attention as a sustainable alternative, offering the potential to reduce emissions and sequester carbon. This study aims to explore public perceptions of engineered wood, focusing on how these perceptions shape preferences and interest in its application for residential construction. The study does not evaluate technical characteristics directly, but rather community interpretations of them. A mixed-methods approach was employed, beginning with qualitative research through online questionnaires that featured open-ended questions designed to capture homeowners and prospective buyers preferences. The responses were then analyzed using content analysis to identify emerging themes. In the second phase, quantitative research was conducted by distributing closed-question questionnaires informed by the findings from the initial phase. The data was analyzed using factor analysis, distribution analysis, and multivariate regression techniques. The study identified three key dimensions influencing material preferences: sustainability, material durability, and material performance. Additionally, three significant dimensions related to construction characteristics were uncovered: design appreciation, construction methods, and material availability. These findings provide valuable insights for the integration of engineered wood into residential construction, offering a pathway to more sustainable building practices.